Plant ribosome recycling factor homologue is a chloroplastic protein and is bactericidal in Escherichia coli carrying temperature-sensitive ribosome recycling factor - Rolland, Norbert (The National Academy of Sciences, 1999)
We have isolated a protein, mature RRFHCP, from chloroplasts of spinach (Spinacia oleracea L.) that shows 46% sequence identity and 66% sequence homology with ribosome recycling factor (RRF) of Escherichia coli. RRF recycles ribosomes through disassembly of the posttermination complex. From the cDNA analysis and from the amino-terminal sequencing of the isolated protein, the mature RRFHCP was deduced to have a M(r) of 21,838 with 193 aa. It lacks the 78-aa chloroplast targeting sequence encoded by the RRFHCP cDNA sequence. The RRFHCP synthesized in vitro was imported into isolated chloroplasts with simultaneous conversion to the mature RRFHCP. Transcription of the gene coding for RRFHCP was not dependent on light, yet it was limited mostly to photosynthetic tissues in which only one transcript size was detected. Mature RRFHCP exerted a bactericidal effect on E. coli carrying temperature-sensitive RRF at the permissive temperature whereas wild-type E. coli was not affected.